China's outward investment activity: Ambiguous findings in the literature and empirical trends in greenfield investments. (12th November 2021) - Yang, Ruilin; Bathelt, Harald
Abstract: With the rapid increase of China's outward foreign direct investments (OFDIs) since the early‐2000s, a growing body of literature has developed that investigates investment processes and their underlying motivations and tendencies. Three important findings emerge from this literature. First, it has been noted that the generation of market and resource access have been key drivers of investment activity. Second, China's OFDIs have accordingly focused on mature manufacturing and natural resource sectors. Third, a large proportion of OFDIs is assumed to have been directed to neighboring countries in East Asia or other developing economies, for instance in Africa. However, a literature review reveals limitations in prior studies with respect to measurement biases, database incompatibilities, the neglect of a knowledge perspective, and a lack of sectoral differentiation. Descriptive analysis based on a comprehensive firm‐level data set of greenfield investments shows that previous findings are only partial. According to fDi Markets data from 2003 to 2016, OFDIs from China are more diversified and widespread than assumed. Many recent investments have a distinct knowledge motivation, are focused on high‐tech and business service sectors and non‐manufacturing functions, and are directed toward developed economies.